THEORETICAL FOUNDATIONS OF THE CLIL METHOD AND ITS ROLE IN INTERDISCIPLINARY INTEGRATION IN FOREIGN LANGUAGE TEACHING (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This study examines the theoretical foundations of Content and Language Integrated Learning (CLIL) and analyzes its role in fostering interdisciplinary integration within foreign language teaching in philological higher education. The growing demand for graduates who possess both advanced language proficiency and subject-specific knowledge has intensified interest in pedagogical models that transcend traditional disciplinary boundaries. CLIL is conceptualized as an educational approach in which a foreign language is used as a medium for learning non-linguistic content, enabling the simultaneous development of linguistic competence and cognitive-academic skills. The abstract outlines the core theoretical premises of CLIL, including constructivist learning theory, communicative language teaching, cognitive linguistics, and socio-cultural perspectives on learning. Particular attention is given to the dual-focused nature of CLIL, where content mastery and language development are treated as interdependent processes rather than isolated objectives. The study emphasizes the relevance of interdisciplinary integration as a key pedagogical outcome of CLIL, highlighting its capacity to connect linguistic education with disciplines such as history, literature, economics, science, and cultural studies. In the context of philological universities, CLIL is presented as a strategic tool for enhancing students’ academic literacy, critical thinking, and professional communicative competence. The abstract also underscores the methodological significance of CLIL for aligning foreign language teaching with contemporary educational standards and labor market requirements. By synthesizing theoretical perspectives and pedagogical principles, the study positions CLIL as a conceptually grounded and practically relevant approach that supports holistic language education and interdisciplinary learning in higher education.